Serum levels of Activin A: Marker of insulin resistance and cardiovascular risk in prediabetics - Ajay Chauhan; Asmita Gupta; Parul Goyal; Tarun Kumar (Journal of Family Medicine and Primary Care, 2022)
Background: A substantial proportion of health burden in diabetic individuals can be attributed to cardiovascular complications. The increasing risk of cardiovascular complications along the spectrum of dysglycemia warrants the need to devise novel markers for early assessment and management. Activin A is a multifunctional cytokine with an important role in glucose homeostasis and vascular diseases. It can thus serve as a guide for early identification of cardiovascular disease (CVD) risk in prediabetes. Objective: The aim of the study was to measure serum levels of activin A in prediabetics, compare them with normoglycemic controls and find the correlation of activin A with markers of insulin resistance such as the homeostatic model assessment of insulin resistance (HOMA-IR). Methods: Sixty prediabetic patients and similar age-, sex-, blood pressure–, and BMI-matched controls were recruited in the study. In both groups, serum levels of fasting blood glucose and post prandial glucose, glycated hemoglobin (HbA1c) and fasting insulin were measured. HOMA-IR values were calculated. Serum activin A levels were measured in both groups using ELISA. The obtained values were compared between the two groups. Results: The median (IQR) of s. fasting insulin (mIU/L) in the case group was 15.3 (12.2–18.62) which was significantly higher than that in the control group, which was 6 (4.2–7.3). The median (IQR) of s. activin A (ng/mL) in the case group was 263.55 (227.18–279.56) which was significantly higher than that in the control group, which was 159.9 (150.73–178.75) (P < 0.001). There was a very strong positive correlation of s. activin A (ng/mL) with s. fasting insulin (mIU/L) and HOMA-IR (rho = 0.67 and 0.75, respectively, P < 0.001). Conclusion: Activin A, if combined with other atherosclerotic markers, might improve the assessment of insulin resistance and cardiovascular risk in prediabetics and lead to focus on lifestyle modifications and preventive medical therapy, thereby contributing to the prevention of CVD-related mortality and morbidity in these patients.